THE DISCOVERY OF THE WEATHER PHENOMENA IN EARLY CHILDHOOD EDUCATION. AN EXPERIMENTAL PROPOSAL (Tabanque. Revista Pedagógica, 2017)
This article present an educational project orientated to the knowledge of the weather phenomena in Early Childhood Education, based on the investigation, the manipulation and the experimentation by young children, and focused more on the love of learning and research that only in acquiring concepts in a purely mechanical form. Our proposal includes the discovery of the physical characteristics of the environment and the affective development, the movement, the habits of corporal control, the communication and the social relations, all it treated from a scientific perspective that defends the importance of science and experimentation in Early Childhood Education. To do this, we turn to the work corners, a methodology that adapts perfectly to the scientific learning that we want to work in the classroom.
Keywords: experimentation; science; weather phenomena; corners; Early Childood Education